Appraisal of Mixed Amorphous Manganese Oxide/Titanium Oxide Sorbents for the Removal of Strontium-90 from Solutions, with Special Reference to Savannah River Site and Chernobyl Radioactive Waste Simulants - Sviatoslav A. Kirillov; Tetiana V. Lisnycha; Oksana I. Pendelyuk (Adsorption Science & Technology, 2006)
Hydrous, amorphous manganese oxide/titanium oxide composites (AMTO) obtained via template synthesis using alkali metal ions as templates have been characterized. Their applicability in remediation technologies has been tested, specifically for 90 Sr removal from Savannah River Site high-level waste supernatants (SHLW) and Chernobyl 4th Block Shelter water (CSW) simulants. Sorption isotherms were used to establish the efficiency of the templating process, while the proton-exchange capacity of AMTO was determined to show that the solids were really protonated. Use of the 90 Sr isotope showed that there was little dependence of the distribution coefficients for AMTO on pH, and at pH < 7, i.e., in neutral and acidic media, AMTO had a much greater affinity for strontium than commercial sorbents. Tests with SHLW and CSW simulants revealed that AMTO is capable of removing more than 99% of 90 Sr from such wastes. Hence, it could be useful for solving decontamination problems.